Pain in photodynamic therapy - Mircea Tampa; Maria Isabela Sârbu; Mădălina-Irina Mitran; Cristina-Iulia Mitran; Adrian Dumitru; Vasile Benea; Simona-Roxana Georgescu (Journal of Mind and Medical Sciences)
Photodynamic therapy is a modern treatment with applications in several medical specialties, which has been intensely studied in the last years. The main indications in dermatology are actinic keratosis, superficial basal cell carcinoma and Bowen's disease- common skin disorders in which photodynamic therapy proved its efficacy. At present, the use of photodynamic therapy for the treatment of other skin disorders is profoundly researched. Pain is the most common and redoubtable adverse effect of photodynamic therapy and it is the most important factor affecting the patient's adherence to treatment. The aim of this article is to look over the most recent medical studies regarding pain in PDT, with emphasis on the factors affecting the occurrence of pain and the most recent strategies for controlling photodynamic therapy- related pain.